Acculturative stress and achievement motivation: the moderating role of immigrant mothers’ Korean proficiency in South Korean multicultural adolescents - Jin, Yuanying; Ahn, Hyun Seon (Frontiers in Psychology, 2025)
IntroductionThis study explores the impact of acculturative stress, mothers’ Korean language proficiency, and their combined effect on the achievement motivation of multicultural students in South Korea.MethodsThrough hierarchical multiple regression analysis of data from 1,287 ninth-grade multicultural adolescents from the Multicultural Youth Panel Survey (MAPS), the relationships among these variables were examined.ResultsThe findings show that high acculturative stress is linked to lower achievement motivation. Notably, this decline is more significant when students perceive their mothers’ Korean language proficiency to be higher.DiscussionThese findings emphasize the need to critically reassess the effectiveness of current multicultural support policies, which are primarily centered on improving mothers’ language proficiency, to better ensure their effectiveness in addressing targeted challenges and achieving meaningful outcomes. Further research is needed to delve deeper into the dynamics of achievement motivation under conditions of high acculturative stress.